(3CSGS GdeSFhdjI GdeOfjI Yf GdEVQGQ HGdHjFI (B: s (3OQGSI ebGQfI Hjf GdbGfhf Gdjefj h GdbGfhf GdeUQj (B/ s - (3efjQ eMeO CMeO KGHJ GdUdhjs; (3SYjO SdjeGf LHQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2016)
(3JYO GdeSFhdjI GdbGfhfjI Yf GdCVQGQ LRAkG CSGSjkG aj cd fXGe bGfhfj, hjJhba eOi aYGdjI GdfXGe GdbGfhfj Ydi eOi fVhL bhGYO GdeSFhdjI ajg(B. (3HjO Cf GdCVQGQ GdHjFjI JJSe HWHjYI NGUI, MjK JKjQ Jdc GdCVQGQ aj HYV UhQgG GdYOjO ef GdeTGcd GdbGfhfjI, hGdJj Jba GdeSFhdjI GdeOfjI HTcdgG GdJbdjOj YGLRI Yf GSJjYGHgG Ch EjLGO Mdhd YGOdI dgG, eeG jSJdRe JWhjY GdfXGe GdbGfhfj ddeSFhdjI GdeOfjI HMjK jJdGee hGdWHjYI GdNGUI ddVQQ GdHjFj, hcPG JWhjQ Pdc GdfXGe HMjK dG jba YfO MO YdGL GdCVQGQ GdHjFjI HYO MOhKgG, Hd GdMO ef GdCVQGQ hGdCNWGQ GdJj JUjH GdHjFI, hGdYed Ydi efYgG hecGaMJgG hGdhbGjI ef GdJYOj Ydi GdHjFI, hgPG GdJWhjQ jLH Cf jeJO Edi GdCSGS GdbGfhfj ddeSFhdjI GdeOfjI Yf GdEVQGQ HGdHjFI, hbO Je HMK gPG GdehVhY aj gPg GdQSGdI aj KdGKI CHhGH jSHbgG aUd JegjOj(B.s
The legal liability for damages is an essential part of every legal system, and stops over the effectiveness of the legal system over the maturity of the liability rules. However, environmental damage has a particular course, which gives rise to such damage in some forms of many legal problems, which civil liability in its traditional form stands unable to absorb or find fair solutions, which requires adapting the legal system of the civil liability to conform to the special nature of the environmental damage, as well as the development of that system so as not to stop at the treatment of environmental damage after it has occurred, but rather limit the damage and dangers that affect the environment, and work to prevent them before they occur, and this development should be extended to the legal basis of the civil liability for damage to the environment. has been Search this topic in this Doctoral thesis in a three doors preceded by an introductory chapter.
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2016.s
(3HHdjhLQGajG(B: (3UaMGJ (B457-507.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3MeGjI GdHjFIs; (3GdbGfhf GdeOfjs -- (3eUQs; (3GdbGfhf GdeOfjs -- (3Gdjefs; (3JdhK GdHjFIs; (3GdHjFIs; (3GdVQQ GdHjFis; (3GdeSFhdjI GdeOfjIs; (3JMed GdJHYIs; (3eVGQ GdLhGQs; (3GdNWC GdeaJQVs; (3GdeSFhdjI GdehVhYjIs; (3GdNWC hGLH GdEKHGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs